2015
DOI: 10.1002/cncr.29672
|View full text |Cite
|
Sign up to set email alerts
|

Psychological effects of androgen‐deprivation therapy on men with prostate cancer and their partners

Abstract: The clinical benefits of androgen-deprivation therapy (ADT) for men with prostate cancer (PC) have been well documented and include living free from the symptoms of metastases for longer periods and improved quality of life. However, ADT comes with a host of its own serious side effects. There is considerable evidence of the adverse cardiovascular, metabolic, and musculoskeletal effects of ADT. Far less has been written about the psychological effects of ADT. This review highlights several adverse psychologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
91
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 111 publications
(94 citation statements)
references
References 164 publications
(240 reference statements)
2
91
0
1
Order By: Relevance
“…Sexual dysfunction is particularly severe for men treated with ADT Donovan et al, 2015;Schover, 2015). In a recent study with a sample of 250 men on ADT (mean age 69), only 9% reported being sexually active 9 months after starting ADT (Ng et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Sexual dysfunction is particularly severe for men treated with ADT Donovan et al, 2015;Schover, 2015). In a recent study with a sample of 250 men on ADT (mean age 69), only 9% reported being sexually active 9 months after starting ADT (Ng et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The included studies compared cognitive test performance with healthy controls, men with PCa not undergoing ADT, or individual pre-ADT baselines. Although available evidence does not suggest that ADT causes global cognitive dysfunction, the small sample sizes in studies to date preclude exclusion of negative effects of ADT in other cognitive domains (Donovan et al 2015). These impacts need to be confirmed in larger longitudinal controlled studies that attempt to adjust for the influence of other side effects of ADT that may affect cognition, for example, effects on mood and fatigue.…”
Section: Mood and Cognitionmentioning
confidence: 97%
“…Men undergoing ADT generally experience loss of libido, erectile dysfunction and reduced sexual activity (Grossmann & Zajac 2011). Men frequently report an associated perceived loss of masculinity and reduced relational intimacy (Donovan et al 2015).…”
Section: Constitutional Vasomotor and Sexual Symptomsmentioning
confidence: 99%
See 2 more Smart Citations